L’expulsió dels moriscos valencians, segons la Relació de Maximilià Cerdà de Tallada. - LOZANO, JOSEP (Scripta, 2021)
This article is about the Valencian Moorish minority and their expulsion, based on a study of a manuscript text by Cerdà de Tallada about the expulsion of the Valencian Moors in 1609. The text, which is incomplete, contains, nevertheless, numerous facts of historiographical interest and is a remarkable example of the Valencian chronicles from the Baroque period.